Evaluation of Relationship between Serum Liver Enzymes and Hypertension: A Cross-Sectional Study Based on Data from Rafsanjan Cohort Study - Parvin Khalili; Saeedeh Abdollahpoor; Fatemeh Ayoobi; Alireza Vakilian; Hamid Hakimi; Zohreh Rajabi; Zahra Jamali (International Journal of Hypertension)
Background. Hypertension as a major risk factor for cardiovascular diseases is among the leading causes of death worldwide. The relationship between elevated serum levels of liver enzymes and hypertension has been reported in limited studies, and to the best of our knowledge, there are no previous reports in the literature on this issue in the southeast of Iran. Our investigation aimed at evaluating the relation between ALT, AST, GGT, and ALP with hypertension in the Rafsanjan Cohort Study, a city in Kerman Province, Iran. Methods. In this cross-sectional study, we used data obtained from the Rafsanjan Cohort Study (RCS), as a part of the prospective epidemiological research studies in Iran (PERSIAN). The association of the liver enzymes levels with hypertension was investigated using the multivariable logistic regression models. Results. Among 9930 participants, the mean age (±SD) was 49.94 (±9.56) years, and 46.56% were men. The odds of abnormal blood pressure significantly increased along with the higher levels of ALT, GGT, and ALP which remained significant only for ALP after adjustment for all confounding variables in both males and females (OR in males: 1.36, 95% CI = 1.09–1.69, OR in females: 1.25, 95% CI = 1.01–1.54). In subjects with normal levels of ALT, AST, GGT, and ALP, dose-response increases were observed for abnormal blood pressure in both genders. Finally, we found that, among liver enzymes, only elevated ALP was significantly correlated with the odds of stage 1 hypertension and stage 2 hypertension for both genders. Conclusions. In subjects with normal levels of ALT, AST, GGT, and ALP, dose-response increases were observed for abnormal blood pressure in both genders. Increased serum ALP activity was positively associated with increased odds of hypertension in males and females. Therefore, increased ALP could be an early indicator of hypertension.